Panderer to power : the untold story of how Alan Greenspan enriched wall street and left a legacy of recession - Sheehan, Frederick J. (McGraw-Hill, 2010)
A look at the man behind the bubble economies of the last two decades reveals the mix of ambition and poor judgment that compelled the former Fed Chairman, Alan Greenspan, to set policies that enriched Wall Street at the expense of the American economy